2018
DOI: 10.1002/hast.865
|View full text |Cite
|
Sign up to set email alerts
|

On Avoiding Deep Dementia

Abstract: Some people will confront Alzheimer's with a measure of resignation, a determination to struggle against the progressive debilitation and to extract whatever comforts and benefits they can from their remaining existence. They are entitled to pursue that resolute path. For other people, like myself, protracted maintenance during progressive cognitive dysfunction and helplessness is an intolerably degrading prospect. The critical question for those of us seeking to avoid protracted dementia is how best to accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In “On Avoiding Deep Dementia,” Norman Cantor astutely notes that, for some individuals, the concept of “protracted maintenance during progressive cognitive dysfunction and helplessness is an intolerably degrading prospect.” This cannot be argued with. Cantor's solution, however—that in the wake of a dementia diagnosis, patients should have the option to direct, in advance, instructions for voluntary stopping of eating and drinking (VSED) should they develop a state of deep dementia—is more ethically challenging than it may first appear.…”
Section: Other Voicementioning
confidence: 96%
“…In “On Avoiding Deep Dementia,” Norman Cantor astutely notes that, for some individuals, the concept of “protracted maintenance during progressive cognitive dysfunction and helplessness is an intolerably degrading prospect.” This cannot be argued with. Cantor's solution, however—that in the wake of a dementia diagnosis, patients should have the option to direct, in advance, instructions for voluntary stopping of eating and drinking (VSED) should they develop a state of deep dementia—is more ethically challenging than it may first appear.…”
Section: Other Voicementioning
confidence: 96%
“…In the article “On Avoiding Deep Dementia,” Norman Cantor defends a position that I suspect many readers share . In my years writing and speaking on advance directives and dementia, I've found that most people support one of two positions.…”
Section: Other Voicementioning
confidence: 99%
“…I n the article "On Avoiding Deep Dementia," Norman Cantor defends a position that I suspect many readers share. 1 In my years writing and speaking on advance directives and dementia, I've found that most people support one of two positions. They are convinced either that advance choices should control the treatment dementia patients receive or that the welfare of a person with dementia should sometimes take priority over earlier choices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thank you for sharing such a personal and heartfelt essay. 1 I have been asked by the editors to comment. Reading it inspires me to do so in a similarly heartfelt way.…”
Section: Dear Normmentioning
confidence: 99%